Cerebrospinal fluid light and heavy neurofilament level increased in anti‐N‐methyl‐d‐aspartate receptor encephalitis. Issue 8 (17th July 2019) - Li, Jiayu; Gu, Yong; An, Hongwei; Zhou, Zheyi; Zheng, Dong; Wang, Zhanhang; Wen, Zehuai; Shen, Hai‐Ying; Wang, Qi; Wang, Honghao
Abstract: Background: Neurofilaments (Nf) are a series of highly specific scaffolding proteins of neurons. Neurofilament light chains (Nf‐L) and the heavy one (Nf‐H) are subunits of Nf, and they are recognized as potent productions of neural damage. The concentrations of Nf aggrandized significantly in neurological disease including neuromyelitis optica, multiple sclerosis, and Alzheimer's disease. However, whether Nf in cerebrospinal fluid (CSF) elevated in anti‐ N ‐methyl‐d ‐aspartate receptor (NMDAR) encephalitis is unclear. Here, we aimed to detect whether CSF Nf is altered in NMDAR and whether changes in CSF Nf can serve as an objective and effective biomarker to evaluate disease severity and prognosis. Methods: We collected 24 anti‐NMDAR encephalitis patients, 11 viral meningoencephalitis/encephalitis (VM) patients, and 21 controls in this study. CSF Nf‐L, Nf‐H, and cytokine levels (IL‐1β, IL‐6, and IL‐17A) were determined by enzyme‐linked immunosorbent assay (ELISA) and compared between groups. We evaluated patients' clinical outcomes or prognosis according to modified Rankin scale (mRS) score. Results: Compared with controls, both CSF Nf‐L and Nf‐H levels were significantly increased in anti‐NMDAR encephalitis patients. While compared with VM patients, only Nf‐L were increased in anti‐NMDAR encephalitis patients. Moreover, CSF Nf‐L were positively correlated with concentration of cytokines (IL‐1β, IL‐17A) and mRS scores in anti‐NMDAR encephalitis patients. After treatment, both CSF Nf‐L and Nf‐H levels decreased. Furthermore, the Nf‐L during follow‐up positively correlated with 3‐month mRS scores, and ΔNf‐L positively correlated with ΔmRS. Conclusions: Briefly, CSF Nf‐L levels notably increased in anti‐NMDAR encephalitis patients in acute phase and positively correlated with disease severity. It could be considered as a useful indicator for clinical outcomes and prognosis. Abstract : CSF Nf‐L and Nf‐H were significantly increased in NMDAR patients. After treatment, both CSF Nf‐L and Nf‐H levels decreased. Nf‐L at acute stage was positively related with max mRS score. Furthermore, the Nf‐L during follow‐up was still positively correlated with 3‐month mRS scores and ΔNf‐L positively correlated with ΔmRS scores.